2017
DOI: 10.1021/acs.nanolett.7b04932
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Hydrodynamic Heat Conduction and Knudsen Minimum in Graphite

Abstract: In the hydrodynamic regime, phonons drift with a nonzero collective velocity under a temperature gradient, reminiscent of viscous gas and fluid flow. The study of hydrodynamic phonon transport has spanned over half a century but has been mostly limited to cryogenic temperatures (~1 K) and more recently to low-dimensional materials. Here, we identify graphite as a three-dimensional material that supports phonon hydrodynamics at significantly higher temperatures (~100 K) based on first-principles calculations. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
143
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(157 citation statements)
references
References 69 publications
13
143
1
Order By: Relevance
“…More recently, it has been suggested that the temperature window for phonon hydrodynamics is much wider in graphene (9) and other 2D materials (19) due to strong normal scattering involving the flexural mode. A similar prediction has been made for graphite, which exhibits a phonon dispersion resembling that of graphene due to the weakness of its interlayer van der Waals interactions (20).…”
Section: Main Textsupporting
confidence: 72%
See 1 more Smart Citation
“…More recently, it has been suggested that the temperature window for phonon hydrodynamics is much wider in graphene (9) and other 2D materials (19) due to strong normal scattering involving the flexural mode. A similar prediction has been made for graphite, which exhibits a phonon dispersion resembling that of graphene due to the weakness of its interlayer van der Waals interactions (20).…”
Section: Main Textsupporting
confidence: 72%
“…The size of the second sound window depends on the concentration of defects, such as isotopes, which contribute to umklapp scattering (6,9,20). While the second sound window in Fig.…”
Section: Main Textmentioning
confidence: 99%
“…The peculiar dependence of thermal conductivity on temperature was observed in solid He at low temperature, verifying the existence of phonon Poiseuille flow [11]. Recently these dependences have been predicted at much higher temperature in graphene [3,51,56] and graphite [20], and experimentally observed in SrTiO3 [57].…”
Section: Iv2 Sample With An Infinite Length and A Finite Widthmentioning
confidence: 60%
“…It remains a difficult task to include the spectral phonon properties into the lattice Boltzmann model. A semi-analytical solution of the PBE under Callaway's model has been obtained by using the integral formulation for steady-state hydrodynamic phonon transport in simple geometrical structures [17,24]. Yet it is not realistic to obtain analytical solutions of the PBE as an integro-differential equation for more general geometries.…”
Section: Introductionmentioning
confidence: 99%